Anaplastic Thyroid Carcinoma versus Metastatic SCC: A Diagnostic Dilemma in a Rare Presentation of Post-Radiation Thyroid Swelling - Rao, Vrushab; Zade, Bhooshan (Indian Journal of Medical and Paediatric Oncology, 2024)
A 71-year-old male with type 2 diabetes and hypertension was diagnosed with carcinoma of the pyriform fossa in 2019. The biopsy was reported as a moderately differentiated squamous cell carcinoma, and positron emission tomography-computed tomography (PET-CT) scan showed an fluorodeoxyglucose (FDG)-avid lesion in the pyriform fossa and the aryepiglottic fold with few nodes in level II and level III. The paitent was treated with radical chemoradiotherapy. A follow-up PET-CT scan done in 2022 revealed an FDG-avid soft tissue thickening in the left palatine tonsillar region and an uptake in the thyroid that was reported as not significant. A punch biopsy from the tonsillar fossa lesion revealed squamous cell carcinoma. The lesion was treated as a second primary and treated with radiotherapy with curative intent. The patient was complaining of dysphagia, difficulty in breathing, and weight loss around 6 months after treatment that were addressed medically. There was a significant reduction in size and FDG activity of the ill-defined thickening in the left tonsillar region which was seen in the response-assessment PET done 6 months after RT. A heterogeneously enhancing nodules were seen in both lobes of the thyroid in which the largest one measured 3.5 × 3.1 cm seen in the right lobe. The patient underwent a biopsy from the thyroid that revealed a benign thyroid gland infiltrated by clusters and nests of poorly differentiated malignant cells. The histomorphology was suggestive of a poorly differentiated carcinoma, likely anaplastic carcinoma thyroid, or metastasis of the squamous cell carcinoma. Curative treatment was ruled out in this case due to his comorbidities, pulmonary symptoms, and radiation delivered to the neck.
Keywords: anaplastic thyroid carcinoma; medical oncology; metastatic squamous cell carcinoma; nuclear medicine; pathology; radiation oncology